Mononuclear cobalt(III) azido complex containing a tetradentate amine: one pot synthesis, structure and thermal behavior - Khan, Sumitava (Bangladesh Journal of Scientific and Industrial Research, 2022)
One hexacoordinated mononuclear complex trans-[Co(L)(N3)2] PF6 (1) [L = N,N′-bis(3-aminopropyl)- 1,2-ethanediamine] is prepared by using one-pot reactions of the building units and characterized. X-ray analysis shows that cobalt center in 1 adopts a distorted octahedral geometry with CoN6 chromophore ligated through four N atoms of tetradentate amine (L) and the two N atoms of terminal azides in mutual trans orientation. In the crystalline state, double N-H…N and multiple N-H…F hydrogen bondings result in 2D sheet structure. The compound has a thermal stability up to 193°C. Bangladesh J. Sci. Ind. Res. 57(2), 109-116, 2022